Iodine‐125 seeds to guide removal of impalpable breast lesions: radio‐guided occult lesion localization – a pilot study. Issue 11 (16th March 2016) - Bourke, Anita G.; Taylor, Donna B.; Westcott, Eliza; Hobbs, Max; Saunders, Christobel
Abstract : Background: The aim of this study was to confirm that radio‐guided occult lesion localization using low activity iodine 125 (I‐125) seeds (ROLLIS) could be safely and accurately used for localization and guided excision of impalpable breast lesions in different multidisciplinary settings and to prepare staff for a randomized controlled trial. Method: Preoperative image‐guided localization of 102 lesions using one or two I‐125 seeds with hook‐wire back‐up was performed in 99 participants at two tertiary hospitals. Preoperative core biopsy in 24 lesions was benign or indeterminate (Group A) and malignant in 78 lesions (Group B). Imaging and histopathology findings and re‐excision rates were recorded. Training requirements for new staff and seed handling protocols were refined. Results: All seeds and lesions were successfully removed. In five of 23 Group A participants, malignancy on final pathology required definitive surgery for positive margins. The re‐excision rate in Group B was 17%. Overall re‐excision rate was 18%. Thirty‐seven clinical staff members were trained. Sentinel node localization was successful in all 76 cases. Seeds of low activity were successfully used. Conclusion: The ROLLIS technique using a lower dose (∼2 MBq) seed is safe, effective and can easily be adopted in a large multi‐disciplinary setting.